Coverage of vertebrate species distributions by Important Bird and Biodiversity Areas and Special Protection Areas in the European Union. (October 2016) - Kukkala, A.S.; Santangeli, A.; Butchart, S.H.M.; Maiorano, L.; Ramirez, I.; Burfield, I.J.; Moilanen, A.
Abstract: The European Union (EU) has an extensive protected area network, including Special Protection Areas (SPAs) designated under the Birds Directive. Important Bird and Biodiversity Areas (IBAs) are sites of international significance for birds identified by BirdLife International. Here, we perform EU-wide terrestrial spatial conservation prioritizations to evaluate the coverage of IBAs by SPAs, and the coverage of bird and other vertebrate distributions by IBAs and SPAs. We then investigate the distribution of potential locations for expanding the SPA network that maximize bird species' representation, and the coverage of these locations by IBAs. On average, SPAs cover 23% of the EU-wide distribution of each bird species and 25% of the distributions of amphibians, reptiles and mammals together, while IBAs provide marginally greater coverage. Overall, 76% of terrestrial IBAs in the EU are completely or partially covered by SPAs, and 66% of the IBA network area is covered by SPAs. Our results suggest that SPA designation has been significantly informed by data on the location of IBAs. While IBAs are identified using data on particular bird species of conservation concern, they also tend to have high EU-wide representation of other vertebrates. The designation of new or expanded SPAs covering a relatively small amount of currently unprotected land (particularly in the southern EU) would substantially increase SPA coverage of bird species ranges. Our analysis provides insights on the current contribution that these sites make to conserving vertebrates across the EU, and future possibilities for efficiently expanding the network. Highlights: IBAs have informed the designation of SPAs in the EU. Coverage of species' distributions by IBAs and SPAs has not previously been assessed. IBAs and SPAs provide high coverage of vertebrate species' distributions. IBAs contain most locations that maximize vertebrate species representation. Mean species' coverage by SPAs could be almost doubled with moderate SPA expansion.